Identification of subclinical mastitis caused by Mycoplasma spp. from screenings of bulk tanks - Joaquim, S. F. [UNESP]; Guimaraes, F. F. [UNESP]; Salina, A. [UNESP]; Junqueira, N. B. [UNESP]; Gomes, E. N. [UNESP]; Langoni, H. [UNESP] (Arquivo Brasileiro Medicina Veterinaria Zootecnia, 2018)
Mastitis caused by Mycoplasma spp., regardless of species, are considered highly contagious pathogens and, usually was not responsive to antimicrobial therapy. Five dairy herds, comprising 489 animals and 1,956 mammary glands, were used in this study. Milk samples were obtained from bulk tanks and subjected to polymerase chain reaction (PCR) for the identification of Mollicutes, Mycoplasma spp., and Mycoplasma bovis. Moreover, individual samples from cases of clinical and subclinical mastitis in quarters of the dairy herds' animals that yielded a positive PCR upon bulk tank analysis were subjected to molecular analysis. Only one bulk tank was positive for class Mollicutes by PCR. All positive samples classified as mastitis teats had their DNA extracted and tested by PCR for both class Mollicutes and M. bovis. Of these, two (2.08%) were positive for Mycoplasma genus, although none was positive for M. bovis. This result suggests that the PCR of bulk tanks is a viable tool in monitoring and preventing mastitis infections caused by Mycoplasma spp.
Keywords: milk quality; polymerase chain reaction; dairy herds